Investigating the Role of Entrepreneurship Education on the Technopreneurship Intention of Generation Z Vocational Students: Why Do Digital Business Literacy and Digital Financial Literacy Matter? - Hasan, Muhammad; Tahir, Thamrin; Nurjannah,; Aeni, Nur; Kang, Hyunsuk (Journal of Technical Education and Training, 2025)
Entrepreneurship plays a central role in the economy as a driver of innovation, economic growth, and job creation. Therefore, entrepreneurship education at various levels, including in vocational schools and colleges, is very important to empower the younger generation, especially Generation Z, to have the competencies and entrepreneurial spirit that are relevant to the digital era. This study aims to explore the role of digital business literacy and digital financial literacy as moderating variables in the relationship between entrepreneurship education and technopreneurship intentions among Generation Z students at the vocational level. The approach used is quantitative with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on 657 respondents obtained through accidental sampling techniques. The test results show that all hypotheses proposed in the research model are significantly accepted (p < 0.05), including the direct effect of entrepreneurship education on technopreneurship intentions and the positive moderating role of digital business literacy and digital financial literacy. These findings provide theoretical contributions to the development of a digital entrepreneurial intention model, as well as practical contributions in designing entrepreneurship policy interventions and curricula that are more adaptive to the needs of Generation Z students at the vocational level in the digital era.